New Inscriptions on Instrumenta from the Northern Periphery of the Byzantine World - Andrey Vinogradov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2022)
Introduction. Byzantine inscriptions on instrumenta, i.e. portable objects (ceramics, tools, objects of personal piety, etc.), usually attract little attention by researchers. Meanwhile, such inscriptions make it easier to look into the world of an ordinary Byzantine. Analysis. The author publishes (in two cases – anew) seven non-standard inscriptions of this type, found recently or previously unpublished. These are the inscriptions on the phylactery, encolpion, amphorae, jug, and bowl. They have a different character: an apotropaic text, a business letter, a humorous poem, an owner’s inscription. Results. These seven monuments open a window to the world of medieval Rhomaios: the fear of the evil eye and the protective prayers, written from hearing; the cheerful world of wine and wine drinking during the voyage and on a bet; jokes about a broken cup, often expressed in verses, that the Byzantines used for any purpose, including the owner’s inscriptions; the world of merchants, who send their goods overseas, take care of its safety and the well-being of sailors. These inscriptions are distinguished by the peculiarities of spelling and style, which make it possible to better imagine the ordinary Byzantine environment. The travelling of the inscriptions on instrumenta, including pilgrims’ inscriptions, reflect, among other things, the ways of spreading Greek writing.